Medical consultation and communication with a family doctor from the patients’ perspective – a review of the literature - Marcinowicz, Ludmiła; Górski, Stanisław (Family Medicine & Primary Care Review, 2016)
The modern understanding of the quality of healthcare takes into account new roles that were granted to patients, including the possibility to assess healthcare based on their experience. A review of the literature shows that among the basic dimensions which serve to measure patients’ satisfaction, issues related to communication are essential. The aim of the study is to determine the aspects of communication with a family doctor which are particularly important from the perspective of the patient. A review of the literature from the years 2000–2016 on communication with family doctors was performed, including articles based on both quantitative and qualitative studies. The main source of the data was the English-language online database PubMed, in which articles were searched for based on such key words as: “medical consultation”, “family doctor”, “general practitioner”, “communication”, “patient’s perspective”. Furthermore, information was searched for in Polish-language journals, books and textbooks for physicians, using a method of manual screening. Analysis of the literature allowed for the identification of the following aspects of communicating with a family doctor perceived by patients: the experience of patients, establishing rapport with a patient, listening, informing a patient, non-verbal behavior, use of a computer during a visit, communication issues from older patients’ perspective, and the relationship between communication and dissatisfaction with care. In summary, the problems of communication between the patient and a family doctor are complex and diverse. The patients’ perspective, with regard to expectations and satisfaction with various aspects of care, including communication, is an important indicator of the quality of care delivered by a family physician.